Analisis Pengaruh Empowerment Karakteristik Individu dan Budaya Kerja Terhadap Kepuasan Kerja (Studi Kasus Karyawan PT BSM Belitung Timur) - Pita Damayanti (JURNAL ILMIAH EDUNOMIKA, 2021)
This research was conducted to see the effect of empowerment variables on individual characteristics and work culture on job satisfaction in the case study of PT. BSM East Belitung. In this study using quantitative descriptive methods and primary data using a questionnaire distributed to employees / respondents. The sample was calculated using the Solvin formula, namely 97 respondents. The sampling technique in this research is positive sampling technique. Data obtained from distributing questionnaires which were then processed using SPSS. Analysis of the data in this study using multiple linear regression analysis which shows the results of the study, namely: empowerment of individual characteristics and work culture is significant on job satisfaction.